2015
DOI: 10.1371/journal.pone.0142341
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Conductive Hearing Loss Leads to Cochlear Degeneration

Abstract: Synapses between cochlear nerve terminals and hair cells are the most vulnerable elements in the inner ear in both noise-induced and age-related hearing loss, and this neuropathy is exacerbated in the absence of efferent feedback from the olivocochlear bundle. If age-related loss is dominated by a lifetime of exposure to environmental sounds, reduction of acoustic drive to the inner ear might improve cochlear preservation throughout life. To test this, we removed the tympanic membrane unilaterally in one group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 57 publications
2
41
1
1
Order By: Relevance
“…There is evidence that CHL through malleus removal does not lead to sensorineural hearing loss ( Tucci et al., 1999 ). However, a recent study investigated the vulnerability of cochlear innervation following CHL through otitis media in mice ( Liberman, Liberman, & Maison, 2015 ). Oval window removal can cause loss of inner hair cell afferent innervation, but this effect is only pronounced for cochleotopic positions above 5 kHz ( Liberman et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that CHL through malleus removal does not lead to sensorineural hearing loss ( Tucci et al., 1999 ). However, a recent study investigated the vulnerability of cochlear innervation following CHL through otitis media in mice ( Liberman, Liberman, & Maison, 2015 ). Oval window removal can cause loss of inner hair cell afferent innervation, but this effect is only pronounced for cochleotopic positions above 5 kHz ( Liberman et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…10). In the adult ear, prior studies from our group have shown that 1) surgical lesions to the LOC and MOC systems can lead to synaptopathy in the IHC area (Maison et al, 2013; Liberman et al, 2014) and that chronic sound deprivation by removal of the eardrum can also lead to dramatic loss of LOC innervation density as well as IHC synaptopathy (Liberman et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…A growing number of animal studies show that noise exposure can cause a loss of auditory nerve fibers (ANFs) without elevating hearing detection thresholds or affecting the audiogram (Kujawa & Liberman, 2015;Liberman, 2015;Liberman, Liberman, & Maison, 2015). Noise exposure that leaves cochlear mechanical responses intact can produce a rapid loss of as many as 40%-60% of the ANF synapses driven by cochlear inner hair cells (cochlear synaptopathy), which carry the ascending signal up the auditory pathway (Kujawa & Liberman, 2006.…”
Section: Individuals Differ In Their Ability To Encode Fine Temporalmentioning
confidence: 99%